The Impact of Wordwall.net on Vocabulary Achievement of Junior High School Students - Dinda Laurenza Zetta Setiawan; Muhammad Haikal Attabik (International Journal of Research in Education, 2026)
This study aims to assess the effectiveness of Wordwall.net in improving seventh-grade students' vocabulary in junior high school. Vocabulary is an essential element of language learning because it helps students understand and express ideas in English. However, many students still struggle to master vocabulary due to limited practice and less engaging learning materials. Therefore, the use of interactive digital tools such as Wordwall.net is expected to help create a more interesting learning environment and support students’ vocabulary development. This study employed a quantitative quasi-experimental design with two groups: the experimental and control groups. The research samples consisted of class VII B (35 students) as the experimental group, which learned vocabulary using Wordwall.net, and class VII A (33 students) as the control group, which learned without using Wordwall.net. The instruments used to collect the data were a pre-test and a post-test with different questions but based on the same test grid to ensure consistency in measurement. The data were analyzed using SPSS 29. The results show a significant difference in post-test scores between the experimental group (79.29) and the control group (56.97). The significance value (Sig. 2-tailed) was < 0.001, which is lower than 0.05, and the effect size was 1.45, indicating a strong effect. Thus, Wordwall.net significantly improved seventh-grade students’ vocabulary.